ATR is essential for preservation of cell mechanics and nuclear integrity during interstitial migration - Gururaj Rao Kidiyoor (Nature Portfolio, 2020)
The nucleus is a mechanically stiff organelle of the cell and the DNA damage response protein ATR can localize to the nuclear envelope upon mechanical stress. Here, the authors show that ATR may contribute to the integrity of the nuclear envelope and may play a role in cell migration.